Facial Feminization Surgery: A Review of 220 Consecutive Patients - Parag Shashank Telang (Indian Journal of Plastic Surgery)
Background Facial feminization surgery (FFS) is a combination of facial bony and soft tissue surgeries designed to modify and convert a masculine face to feminine. One’s face plays a very central role in gender incongruence and FFS helps patients overcome this. There are prominent differences between the male and the female facial anatomy (bony and soft tissue) which can be surgically altered to change the visual perception of the face. Methods The author presents the method used at his center for treating 220 patients of gender incongruence requesting FFS from June 2016 to June 2019. The alterations to known methods of forehead contouring, hairline lowering, and jaw shave adopted by his team are discussed. He also presents the logic of performing the entire FFS in two stages at an interval of 7 to 10 days. Results A total of 220 cases of FFS are presented, along with surgical details of techniques used, the sequence and staging of procedures performed, and the results obtained. A two-staged approach to FFS is proposed to maximize the recovery and minimize complications and promote faster healing. Different methods of forehead contouring are also explained in detail. Conclusions FFS is a very rewarding surgery for the plastic surgeon and has high patient satisfaction rate. With proper training in craniomaxillofacial and soft tissue surgery, it is possible for the plastic surgeon to be the main team leader for this procedure. A two-stage approach is highly recommended.